Efektivitas Strategi Inquiry Dalam Meningkatkan Hasil Belajar Mahasiswa Mata Kuliah Sistem Informasi Perbankan - Nurbaiti Sirait (AT-TAWASSUTH: Jurnal Ekonomi Islam, 2018)
This study aims to know the student learning outcomes by using brainstorming method, conventional methods and knowing the difference between both of the 2 learning methods in the course of banking information systems . The objects are the students of semester V of Islamic Economics Program about 62 students with random sampling. In this research, the researchers succeeded in obtaining the values for the normality test in the experimental class on the pre-test obtained Lstat = 0.122, while in the post-test Lstat= 0,093 and for the control class on the pre-test Lstat = 0.129, while in the post-test 0.102, then the Ltabel = 0.159 with the two classes having the same number of students, means the data is normally distributed. For homogeneity test the value of pre-test obtained Fstat = 1.61 and the value of post-test diperleh Fhitung = 1.17, while for Ftabel = 1.84, which means the two samples each homogeneous. As for the hypothesis test t obtained price t count = 2.389 and ttable = 2,000. Which means t-stat > t-table, that is 2,389 > 2,000 means there are differences in learning outcomes in banking information system courses that are taught by brainstorming and conventional methods.